R＆D practice of self-service platform portal for small and medium-sized enterprises - Min YAN; Zeng YIN; Xi YANG (Dianxin kexue)
In the era of rapid development of the internet,the office methods and production methods of enterprises is constantly changing.However,the traditional VPN leased line can’t meet the needs of increasingly intensive business adjustment,network status monitoring in real time and adjustment of service traffic.With the development of SDN/NFV technology,operators are beginning to explore the application scenarios of this technology in the government-enterprise leased line.Independent research and development portal for small and medium-sized enterprises with SD-WAN on-demand network which operators provided was mainly researched.The connotation of portal,the location of portal in the architecture of on-demand network,needs analysis and R＆amp;D practice of portal development were analyzed.